2006
DOI: 10.1158/0008-5472.can-05-3719
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor-1-Dependent Repression of E-cadherin in von Hippel-Lindau Tumor Suppressor–Null Renal Cell Carcinoma Mediated by TCF3, ZFHX1A, and ZFHX1B

Abstract: A critical event in the pathogenesis of invasive and metastatic cancer is E-cadherin loss of function. Renal clear cell carcinoma (RCC) is characterized by loss of function of the von Hippel-Lindau tumor suppressor (VHL), which negatively regulates hypoxia-inducible factor-1 (HIF-1). Loss of E-cadherin expression and decreased cell-cell adhesion in VHL-null RCC4 cells were corrected by enforced expression of VHL, a dominant-negative HIF-1A mutant, or a short hairpin RNA directed against HIF-1A. In human RCC bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
319
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 396 publications
(335 citation statements)
references
References 30 publications
(33 reference statements)
16
319
0
Order By: Relevance
“…14 Recently, VHL was shown to promote the transcription of E-cadherin via HIF-dependent activation of E-cadherin-specific transcriptional repressors. [15][16][17] Thus, a loss of VHL in CC-RCC results in the hyperactivation of HIF that triggers the expression of E-cadherin repressors, which in turn attenuates the expression of E-cadherin. 15-17 E-cadherin, a homophilic adhesion molecule associated with catenins that functions as a major component of cell junctions in polarized epithelial cells, is an established tumor suppressor.…”
mentioning
confidence: 99%
“…14 Recently, VHL was shown to promote the transcription of E-cadherin via HIF-dependent activation of E-cadherin-specific transcriptional repressors. [15][16][17] Thus, a loss of VHL in CC-RCC results in the hyperactivation of HIF that triggers the expression of E-cadherin repressors, which in turn attenuates the expression of E-cadherin. 15-17 E-cadherin, a homophilic adhesion molecule associated with catenins that functions as a major component of cell junctions in polarized epithelial cells, is an established tumor suppressor.…”
mentioning
confidence: 99%
“…Similarly, Evans et al 107 demonstrated that knockdown of pVHL resulted in E-cadherin suppression via HIF-dependent induction of E2 box-dependent transcriptional repressors Snail and SIP1, and Krishnamachary et al 108 reported that HIF-1 activation in VHL-deficient cells downregulated Ecadherin, led to the loss of cell-cell adhesion and promoted epithelial to mesenchymal transition through the induction of transcriptional repressors TCF3, ZFHX1A and ZFHX1B/SIP1. Therefore, cellular changes, such as loss of intercellular junctions and epithelial de-differentiation involving HIFdependent as well as HIF-independent molecular pathways 48,[106][107][108] in addition to HIF-dependent and -independent alterations in p53 or NF-kB activity, 34,35,49,51 HGF signaling, 45,50,109 and modifications in ECM turnover and re-modeling [42][43][44][45][46][47] create the molecular environment for the development CC-RCC, which most likely requires additional genetic events. The importance of HIF activation in CC-RCC pathogenesis and growth is furthermore underscored by experimental and clinical studies, which demonstrated that inhibition of HIF-a translation by pharmacological targeting of mTOR correlated with reduced tumor growth, 110 and that increased expression of certain HIF target genes, such as CXCR4, as well as E-cadherin suppression was associated with disease progression.…”
Section: Pvhl and Renal Cell Cancermentioning
confidence: 95%
“…When there is up-regulation of HIF-1, a message is sent to the nucleus to down-regulate the expression of e-cadherin (Krishnamachary et al, 2006). E-cadherin is responsible for the formation of focal adhesion complex (Gooding et al, 2004).…”
Section: Mif and Metastasismentioning
confidence: 99%